Implementasi Metode Takrir dalam Meningkatkan Hafalan Al-Qur’an Peserta Didik pada Mata Pelajaran Tahfizh Kelas VC MI Darul Qur’an Sawangan Depok - Millah, Muzayanatul; Pesha, Indry Nirma Yunizul; Muhlisin, Sofian (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study discusses the implementation of the takrir method in improving the memorization of the Qur'an among students of the VC class MI Darul Qur'an Sawangan, Depok. This study aims to find out the application of the takrir method in improving the memorization of the Qur'an among students of the VC MI Darul Qur'an class, the results of the application of the takrir method and its supporting and inhibiting factors. This study uses a descriptive qualitative approach with the type of field research. The data collection technique uses observation, interview, and documentation techniques, using data analysis, data reduction, data presentation, and conclusion. The results of this study show that the application of the takrir method in learning tahfizh in VC class in improving the memorization of the Qur'an has gone well and in accordance with the following learning steps: Bin-Nazhar, Talaqqi, Takrir, Tasmi'. Supporting factors in the application of this method include health, psychological, intelligence, motivation and age. The inhibiting factors are: the reading of the Qur'an is still not good, similar verses, few repetitions, and the absence of a guide.